2008
DOI: 10.1073/pnas.0708965105
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of human errors by maladaptive changes in event-related brain networks

Abstract: Humans engaged in monotonous tasks are susceptible to occasional errors that may lead to serious consequences, but little is known about brain activity patterns preceding errors. Using functional MRI and applying independent component analysis followed by deconvolution of hemodynamic responses, we studied error preceding brain activity on a trial-by-trial basis. We found a set of brain regions in which the temporal evolution of activation predicted performance errors. These maladaptive brain activity changes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
393
4
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 430 publications
(432 citation statements)
references
References 52 publications
27
393
4
2
Order By: Relevance
“…Previous research investigating the role of the DMN preceding task performance supports our findings that a lower prestimulus DMN state is beneficial for cognitive task performance (Eichele et al., 2008; Esterman et al., 2013; Li et al., 2007; Sali et al., 2016; Soravia et al., 2016; Weissman et al., 2006). In the current study, participants performed the mental rotation task in a sparse event‐related design and were thus not presented with visual input for a longer period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research investigating the role of the DMN preceding task performance supports our findings that a lower prestimulus DMN state is beneficial for cognitive task performance (Eichele et al., 2008; Esterman et al., 2013; Li et al., 2007; Sali et al., 2016; Soravia et al., 2016; Weissman et al., 2006). In the current study, participants performed the mental rotation task in a sparse event‐related design and were thus not presented with visual input for a longer period.…”
Section: Discussionmentioning
confidence: 99%
“…In one early study, it was shown that attentional lapses were associated with a higher task‐induced DMN activation on a selective attention task (Weissman et al., 2006). Furthermore, it has been shown that a higher prestimulus DMN activation precedes errors on a go/no‐go task (Li et al., 2007), as well as errors in a Flanker task (Eichele et al., 2008), compared to correct task performance. Since these early studies, prestimulus DMN effects have been investigated more extensively, showing a more differential role of these effects on task performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2008). This method entails estimating the HRF by forming the convolution matrix of the stimulus onsets and multiplying its pseudoinverse with the IC time course.…”
Section: Methodsmentioning
confidence: 99%
“…1) were derived from the Automatic Anatomic Labelling (AAL) atlas implemented in the WFU Pickatlas [54][55][56]. After averaging over the relevant voxels, the mean signal time series were extracted from each ROI and were used to create individual ROI-to-ROI connectivity matrices between regions corresponding to DMN, DAN, VAN and SN.…”
Section: Functional Resting-state Connectivity Analysismentioning
confidence: 99%